UNSCENTED KALMAN FILTERS AND EXTENDED H FILTER FOR SPACECRAFT ATTITUDE ESTIMATION USING QUATERNIONS - Silva, William Reis; Garcia, Roberta Veloso; Kuga, Hélio Koiti; Zanardi, Maria Cecília (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this work, the attitude determination and the gyros drift estimation using the Uncented Kalman Filter (UKF) and the Second-Order Extended H Filter (SOEH F) for nonlinear systemsÂ will be described. The extended H filter provides a rigorous method for dealing with systems that have model and noise uncertainties. Thus, extended H filter is simply a robust version of the extended Kalman filter because to add tolerance to unmodeled noise and dynamics. The Unscented Kalman Filter transforms a set of points (cloud) through known nonlinear equations and combines the results to estimate the mean and covariance of the state. The points (called sigma-points) are carefully selected on the basis of a specific criterion. The application uses the simulated measurement data for orbit and attitude of the CBERS-2 (China Brazil Earth Resources Satellite). The attitude model is described by quaternions and the attitude sensors available are two DSS (Digital Sun Sensors), two IRES (Infra-Red Earth Sensor), and one triad of mechanical gyros.The results in this work show that one can reach accuracies in attitude determination within the prescribed requirements, besides providing estimates of the gyro drifts which can be further used to enhance the gyro error model. Keywords: Unscented Kalman Filter, Extended H Filter, Attitude Estimation, Gyro Calibration, Nonlinear System